MODEL SISTEM PENUNJANG KEPUTUSAN (DECISION SUPPORT SYSTEM MODEL) UNTUK PERENCANAAN PENGELOLAAN WILAYAH SUNGAI SESUAI UU 7/2004 - Suseno Darsono; Pranoto S.A. (Diponegoro University, 2008)
Total population increase therefore water supply requirement, irrigation water, as well as requirement ofresidential areas are also increase. Many ways in development of water resources management arerequired to fulfill future water requirement, and need minimizing land use changes. Integrated waterresources management planning based on river basins is required. Polices for water resourcesconservation program, exploitation of water resources and control of the water’s destructive force arerequired for optimizing water resources management. A holistic water resources management is requiredfor protecting, maintaining as well as increasing the value of water resources. According to WaterResources Law No. 7 year 2004, a water resources planning for a river basin has to prepare withparticipation of some stakeholders. Many program alternatives of water resources management will beproduced from a water resources management planning process. Thus, the ranking analysis of alternativeprograms needs to be proceeded. Decision Support System (DSS) with weighting optimization model is atool for helping to determine the rank of water resources development programs. The DSS technique needscriteria as basic for prioritizing water resources development programs. Determination weight for eachcriterion and score for each alternative water resources development program are required. Applicationof this model is a priority analysis of water resources development program from JRATUNSELUNA riverbasin for administration district Jepara, Kudus and Demak